SIKAP PEMILIH TERHADAP PASANGAN CALON KEPALA DAERAH MENJELANG PILKADA LANGSUNG DI KOTA BITUNG - Lumolo, Johny (Pusat Penelitian Politik, 2007)
The purpose of General Election including in Local Government (Pemerintah Daerah) is to create a democratic government based on the principle of the people, by the people andfor the people. In so doing, the process of General Election must be colored by transparency and accountability principle. In line with this notion this research portray empirical condition surrounding Local Government General Election (Pemilihan Kepala Daerah) in Bitung Municipality in year 2004. As an explorative study, this research utilizes survey technique to draw respondents' opinion which will be presented in a descriptive analysis method. This research aims to analyze attitudes ofthe voters in determining their preferences, the reason of their decision and the influence ofmoney politics on the voters decision. This research confirms that most of the voters choose the candidates based on three main reasons as they know the candidates very well they believe in the candidates personal character figur and they have an ideological bond with the candidate However the effect of ideology is only apparent among PDI P voters as they consistently choose candidates from PDI P while others voters are likely to choose the candidates based on thefigur On the contrary with the common perception about effect ofmoney politics this research indicates that in this case money politics is less effective in influencing the voters decision to choose the candidates.